Changes in triglyceride-rich lipoprotein particle profiles in response to one-week on a low fat or Mediterranean diet by TCF7L2 rs7903146 genotype: a randomized crossover dietary intervention trial. - Lai, Chao-Qiang.; Gervis, Julie E; Parnell, Laurence D; Lichtenstein, Alice H; Ordovas, Jose M (Tufts University. Tisch Library., 2025)
Keywords: TCF7L2, Mediterranean diet, Triglyceride-rich lipoprotein, Cardiovascular disease, Intervention trial.; Springer Open.